Colocated Objects? a New Challenge to the Intentionalists' Solution to the Grounding Problem - (:unkn) unknown (My University, 2014)
C.S. Sutton (2012) renews the intentionalists' solution to the grounding problem for colocationalism by responding to Karen Bennett's (2004) challenge. This paper aims to show that Sutton's revised approach to the grounding problem is still untenable. I start with a simplistic version of intentionalists' grounding claim. For this simplistic version, I argue that the possible alternative intentions can lead to contradiction in modal properties. Then I introduce Sutton's more sophisticated attempts to solve the grounding problem. I contend that, in order to avoid the similar objection to the simplistic version, Sutton ultimately runs out of resources for a genuine solution.
Keywords: Colocated Objects; Grounding; Intentionalism